Muscle strength assessment of knee flexors and extensors. Comparative study between basketball, football, handball and volleyball athletes - Teixeira, Jorge (2021)
Muscle strength of lower limbs is considered a key factor in handball, basketball, football and volleyball athletes’ performance, as support of specific motor skills and actions. One of the methods used to assess muscle strength is isokinetic dynamometry.